2009
DOI: 10.21608/ejabf.2009.2029
|View full text |Cite
|
Sign up to set email alerts
|

Culture of the Nile tilapia (Oreochromis niloticus) in a recirculating water system using different protein levels

Abstract: ABSTRACThe study investigated the effect of dietary protein levels on growth performance and body composition of the Nile tilapia, Oreochromis niloticus fingerlings (8.0 g), using a recirculating water system. The system consisted of eight rearing concrete tanks, underground plastic tank acts as a clarifier and upper plastic tank acts as a biofilter. The system was supplied with air and water pumps. Fish were fed on four dietary protein levels (20%, 25%, 30% and 35%) to satiaty for 6 days a week for 6 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
1
10
1
2
Order By: Relevance
“…Nile tilapia (Oreochromis niloticus) is an economically important aquatic animal cultured worldwide. Its rapid growth rate, adaptability to a wide range of environmental conditions and ability to grow at low trophic levels make it an excellent candidate for aquaculture, especially in tropical and subtropical regions, including Thailand (Bahnasawy et al 2009). Nile tilapia are capable of adaptation to various habitats and may be a good representative of aquatic animals for studying the impact of polluting toxicants, like AgNP, on local animal health.…”
Section: Introductionmentioning
confidence: 99%
“…Nile tilapia (Oreochromis niloticus) is an economically important aquatic animal cultured worldwide. Its rapid growth rate, adaptability to a wide range of environmental conditions and ability to grow at low trophic levels make it an excellent candidate for aquaculture, especially in tropical and subtropical regions, including Thailand (Bahnasawy et al 2009). Nile tilapia are capable of adaptation to various habitats and may be a good representative of aquatic animals for studying the impact of polluting toxicants, like AgNP, on local animal health.…”
Section: Introductionmentioning
confidence: 99%
“…The PER of this study (1.62 ± 0.06) is in the interval from 1.25 to 1.98 reported by Khattab et al (2000) for Nile tilapia in pond culture. It is also between the range of 1.34 to 1.85 reported for O. niloticus reared in recirculating water system, using feed containing respectively 35% and 20% crude protein content at a stocking density of 60 fish/m 3 (Bahnasawy et al, 2009). Ahmad et al (2004) found PER of 1.92; 1.58 and 1.98 for tilapia fingerlings (20.3 g) reared in concrete tanks using a recirculating system and a diet containing 25; 35 and 45% crude protein respectively.…”
Section: Protein Efficiency Ratiomentioning
confidence: 51%
“…Protein efficiency ratio (PER) is based on the weight gain of a test subject divided by its intake of a particular food protein during the test period (Buamah and Singsen, 1975). According to Bahnasawy et al (2009), fish growth is significantly affected by diet protein level. The PER of this study (1.62 ± 0.06) is in the interval from 1.25 to 1.98 reported by Khattab et al (2000) for Nile tilapia in pond culture.…”
Section: Protein Efficiency Ratiomentioning
confidence: 99%
“…However, dissolved oxygen is a little lower than the optimum need (i.e. above 5 mg/L) for most of the fishes [15], [16]. The main cause behind this lower DO may be because no aerator is used in the tanks.…”
Section: Discussionmentioning
confidence: 97%